The Listener: Love of Money and How It Affects Someone’s Life Especially in Decision Making and Personality - Michella Fellicia Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2019)
My screenplay The Listener is the story of Mike, a guy in his late 20s who loves money and thinks that money can buy happiness. My work’s main idea revolves around loves of money and how it can lead into a bad decision. I used the theory Base of Materialism Theory from Belk and Measurement of Materialism and Money Attitude from Rimple, Srikant, Naseem, and Kumar to construct the personalities of the main character. The purpose of this creative thesis is to increase the awareness that money cannot buy happiness. I used crime as the genre and Heist Flicks as the subgenre because I see a lot of similarities and genre convention with my screenplay’s subject matter of loves of money and money cannot buy someone’s happiness. The story mostly tells about how Mike faces the hardship in making decisions due to his loves of money. Later, he focuses on his prestige by having lots of money. At the end, he realizes that friendship is more important than money. Keywords: The Listener, Love of Money, Prestige, Materialism, Heist Flicks